Value-Based Information Systems and Technologies Governance Quality Assessment - Merchán Rodríguez, Vicente Rolando (2018)
The quality is a degree of excellence, and what is excellent is new. The evaluations of the quality of the organizations, departments, functional areas, activities, products and services have been recognized by the goodness of their results beginning to be mandatory and of increasingly strict application in the search of the fulfilment of its purposes. The quality has been a goal of many countries. In Ecuador, the Constitution establishes that the public administration is governed by principles, among others: the quality. This involves the participation of the people to ensure the actions in the organizational context. The quality has an impact on people, activities, processes and outcomes; all guided toward excellence. An intention of quality (not exclusive from the point of view of the analysis of other models) and at the same time of the Government of the TSI is the application of good practices of the Ibero-American Model [3] and of the standard ISO/IEC 38500 [4], respectively. The proposed quality assessment model exposes the government of TIS as a functional team at the service of the organization of TIS. Therefore, the model is a response to the value-based quality concept on value due to the extent that Ecuador is gaining a growth in the use of technology. The existing literature on EFQM models, Malcolm Baldrige and other authors who support it, was available for this work [5] [6] [7] [8]. In such a way that it is appropriate to identify suitable criterion relations between standards of governance and models of excellence, the criteria and sub-criteria, dimensions and evidence that arise as part of the quality model.